2019
DOI: 10.1016/j.jns.2018.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Burden of subclinical carotid atherosclerosis and vascular risk factors among people living with HIV in Ghana

Abstract: Background-The burden of cardiovascular disease (CVD) among people living with HIV (PLWH) in sub-Saharan Africa is projected to rise due to a rapid epidemiological transition and improved treatment of HIV infection on the sub-continent.Objective-The Evaluation of Vascular Event Risk while on Long-term Anti-retroviral Suppressive Therapy (EVERLAST) Study sought to assess the extent of subclinical atherosclerosis and characterize the nature of CVD risk factors among HIV patients on Antiretroviral therapy (ART) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…Furthermore, enhancing adherence to CVD medicines through mobile health technology as has been shown in the context of stroke in Ghana would all require systematic testing through clinical trials to assess their efficacy and potential implementation in our setting. On a much broader scale, our previous report shows a highly prevalent but poorly controlled hypertension rate in the general population based on evidence gleaned from our HIV‐negative sample . This may explain why we found that HIV per se was not to be independently associated with stroke occurrence in a low endemic country such as Ghana, although the burden of stroke and poor outcomes continue to rise in the subregion due to a myriad of factors hampering the control of key CVD risk factors …”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Furthermore, enhancing adherence to CVD medicines through mobile health technology as has been shown in the context of stroke in Ghana would all require systematic testing through clinical trials to assess their efficacy and potential implementation in our setting. On a much broader scale, our previous report shows a highly prevalent but poorly controlled hypertension rate in the general population based on evidence gleaned from our HIV‐negative sample . This may explain why we found that HIV per se was not to be independently associated with stroke occurrence in a low endemic country such as Ghana, although the burden of stroke and poor outcomes continue to rise in the subregion due to a myriad of factors hampering the control of key CVD risk factors …”
Section: Discussionmentioning
confidence: 67%
“…The Evaluation of Vascular Event Risk while on Long‐term Anti‐retroviral Suppressive Therapy (EVERLAST) Study seeks to characterize the burden of cardiovascular risk among patients with HIV on cART in Ghana. We have shown in a recent report among Ghanaian PLWH that hypertension was associated with subclinical atherosclerosis at a carotid intimal media thickness (CIMT) cutoff value of 1.00 mm . Carotid atherosclerosis is a harbinger of MACE in the HIV population .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…37 A higher prevalence has been reported, however, in both a Senegalese cohort (28%) and a recent Ghanaian cohort (40%), which may be due to differences in baseline age and sex. 9,15,38 These findings underscore the fact that the burden of hypertension is likely to rise with an aging HIV population and should attract proportionate public health and clinical response to curb the projected increase in prevalence and its associated disease burden.…”
Section: Comparison With Previous Researchmentioning
confidence: 89%
“…7 Routine assessment and monitoring of CVD risk among HIV patients globally is generally suboptimal 8 with only one published report from Ghana, in particular. 9 This current study sought to fill this gap in knowledge and to estimate the CVD burden of HIV patients presenting for routine visits at the largest HIV clinic in central Ghana.…”
Section: Introductionmentioning
confidence: 99%